Comparative Analysis of Volatile Components in Chinese Strong-Aroma Baijiu of Different Ages - Zhu, Mingxuan (International Journal of Agriculture and Food Sciences Research, 2026)
In this study, Chinese strong-flavor Baijiu was used as the research object. Volatile compounds were analyzed in newly distilled liquor samples and strong-flavor Baijiu samples aged in stainless steel tanks for 6, 12, 18, and 24 months, respectively. The results demonstrated that organic acids, higher alcohols, and aromatic compounds were continuously generated and accumulated during the aging process, which contributed to the mellow cellar aroma, honey aroma, and aged aroma of the liquor. In addition, the contents of ethyl butyrate, 1-hexanol and other components exhibited a steady upward trend, while acetaldehyde showed a slight fluctuation followed by an increase. Overall, the aging process was characterized by decreased esters, increased acids and alcohols, and coordinated flavor development, verifying the optimizing effect of aging on the flavor profile of Baijiu. This study provides key data support for elucidating the aging mechanism of strong-flavor Baijiu.